Сезонная динамика количественных показателей развития фитопланктона на верхнем участке реки Южный Буг - Белоус, Е.П.; Шевченко, Т.Ф.; Клоченко, П.Д. (Гидробиологический журнал, 2014)
Изучена сезонная динамика видового богатства, численности, биомассы и комплекса доминирующих видов фитопланктона на верхнем участке р. Южный Буг в районе г. Хмельницкого. Отмечено несколько пиков развития водорослей на протяжении года. Максимум видового богатства, вызванный резким увеличением количества видов зеленых водорослей, а также пик численности, обусловленный развитием синезеленых, зарегистрированы в июле. Пики биомассы фитопланктона за счет интенсивного развития диатомовых и динофитовых водорослей наблюдали в июне и сентябре. Досліджено сезонну динаміку видового багатства, чисельності, біомаси та комплексу домінуючих видів планктонних водоростей на верхній ділянці р. Південний Буг у районі м. Хмельницького. Виявлено декілька піків розвитку водоростей протягом року. Підйом видового багатства фітопланктону, зумовлений різким збільшенням кількості видів зелених водоростей, а також пік його чисельності, спричинений розвитком синьозелених водоростей, зареєстровані у липні. Піки біомаси за рахунок розвитку діатомових і динофітових водоростей спостерігали у червні і вересні. Seasonal dynamics of plankton algae species number, their numbers and biomass, and also of the complex of dominant species, were studied in the upper section of the Southern Bug River located within the territory of the town of Khmelnitskiy. Several peaks of algae development were revealed during the period of investigations. The highest number of phytoplankton species caused by a sharp increase in the number of species of green algae was registered in July. The maximum numbers of phytoplankton conditioned by the development of blue-green algae were observed also in July. Seasonal dynamics of phytoplankton biomass were characterized by the presence of two peaks. The first peak conditioned by the development of diatoms was registered in June, whereas the second peak caused by intensive development of Dinophyta and Bacillariophyta — in September.